2018
DOI: 10.1029/2018ja025480
|View full text |Cite
|
Sign up to set email alerts
|

Magnetospheric Source Region of Auroral Finger‐like Structures Observed by the RBSP‐A Satellite

Abstract: Auroral finger‐like structures appear equatorward of the auroral oval in the diffuse auroral region and contribute to the auroral fragmentation into patches. A previous report of the first conjugate observation of auroral finger‐like structures using a Time History of Events and Macroscale Interactions during Substorms (THEMIS) Ground‐Based Observatories camera and the THEMIS‐E satellite at a radial distance of ∼8 RE showed antiphase oscillations of magnetic and plasma pressures in the dawnside plasma sheet. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The instability mechanism mentioned earlier near the dusk sector provides another potential candidate for wave excitation. Nishi et al () and Shiokawa et al () reported finger‐like auroral brightness structures at postmidnight sectors near the equatorial boundary of an auroral arc. These brightness structures were organized latitudinally with horizontal‐scale sizes ranging from 15–100 km, moved eastward with slow speeds of 150–400 m/s, and were considered as auroral fragmentation into patches.…”
Section: Resultsmentioning
confidence: 97%
“…The instability mechanism mentioned earlier near the dusk sector provides another potential candidate for wave excitation. Nishi et al () and Shiokawa et al () reported finger‐like auroral brightness structures at postmidnight sectors near the equatorial boundary of an auroral arc. These brightness structures were organized latitudinally with horizontal‐scale sizes ranging from 15–100 km, moved eastward with slow speeds of 150–400 m/s, and were considered as auroral fragmentation into patches.…”
Section: Resultsmentioning
confidence: 97%
“…However, they focused on signatures of field‐aligned currents, and did not show electron and ion spectra and their pitch‐angle distributions in the source of the auroral arc. Nishi et al (2017, 2018) investigated electron and ion spectra and pressure variations in the source of auroral finger‐like structures in the diffuse auroral region using the Van Allen Probes and THEMIS satellites at a radial distance of 6–8 Re . However, electron and ion spectra, their pitch‐angle distributions, and field variations in the source of auroral arcs and diffuse auroras in the inner magnetosphere have not been well understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Using these magnetic field and plasma data, we made the following analysis procedures to obtain the phase relationship of the magnetic and plasma pressures. (1) We subtracted 10‐min running averages of the pressures data from the original data in order to extract variation components with periods of several minutes which are comparable with the time scales of finger‐like structure crossings reported by Nishi et al (, ). (2) For every 1‐hr time segments with 1,201 or 1,202 data points, we calculated power spectra of the variation components of the plasma and magnetic pressures, Δ P t h and Δ P B , respectively, and coherences and phases between these pressures using the fast Fourier transform (FFT).…”
Section: Statistical Data Set and Analysis Methodsmentioning
confidence: 99%
“…This result is consistent with the idea of the pressure‐driven instability advocated by Shiokawa et al (, ). However in the latter event (Nishi et al, ), the phase relationship of the pressure fluctuations was not systematic, differently from the THEMIS‐E conjunction event. This difference of phase relationship of plasma and magnetic pressures between THEMIS‐E (∼8 R E ) and RBSP‐A (∼5.5 R E ) associated with auroral finger‐like structures provided us a strong motivation to systematically investigate the correlation of these pressure variations in the nightside magnetosphere.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation